Antimicrobial susceptibility testing: currently used methods and devices and the near future in clinical practice - Benkova, M.; Soukup, O.; Marek, J. (Journal of applied microbiology, 2020)
Summary Rapid identification of pathogen and its resistance to antimicrobial drugs, and subsequent appropriate antimicrobial treatment are essential for correct patient outcomes. Conventional detection methods of bacterial resistance, such as disc diffusion, broth microdilution and automated instruments, are constantly widely used and primarily standardized. Nevertheless, the results cannot be obtained earlier than 48 h after receiving a sample, which may lead to prolonged use or overuse of broad‐spectrum antibiotics. Hence, there is a drive to develop and introduce novel, faster, standardized, sensitive and specific methods with reliable results into routine microbiological laboratory practice. Recently developed matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) has been introduced in recent years into laboratory practice, and methods based on microfluidics and microdroplets might be introduced in the near future. This review is focused on the methods and instruments in use both currently and in the foreseeable future, applicable to determine antimicrobial efficacy in clinical microbiology laboratories.